Atomoxetine Treatment Outcomes in Adolescents and Young Adults With Attention-Deficit/Hyperactivity Disorder: Results From a Post Hoc, Pooled Analysis - Adler, Lenard A.; Wilens, Timothy; Zhang, Shuyu; Dittmann, Ralf W.; D'Souza, Deborah N.; Schuh, Leslie; Durell, Todd M. (Clinical therapeutics, 2012)
Many children with attention-deficit/hyperactivity disorder (ADHD) continue to experience this disorder as adults, which may, in part, be due to the discontinuity of health care that often occurs during the transition period between late adolescence and young adulthood. Although atomoxetine is reported to be efficacious in both adolescents and young adults, no longitudinal studies have been designed to assess directly the effects of atomoxetine treatment during this transition period. As a first step, we present the results of a post hoc, pooled analysis that compared the efficacy and safety profile of atomoxetine in these 2 patient populations. The aim of the present study was to assess the efficacy and safety profile of atomoxetine treatment in adolescents and young adults with ADHD. A post hoc, pooled analysis was conducted by combining data from 6 double-blind trials (6–9 weeks in duration) that studied adolescents (12–17 years of age; atomoxetine, n = 154; placebo, n = 88; mean final dose = 1.38 mg/kg) and 3 trials (10 weeks in duration) that studied young adults (18–30 years of age; atomoxetine, n = 117; placebo, n = 125; mean final dose = 1.21 mg/kg). Efficacy measures used in these analyses were ADHD Rating Scale (ADHDRS) for adolescents, Conners' Adult ADHD Rating Scale (CAARS) for young adults, and Clinical Global Impressions-ADHD-Severity (CGI-ADHD-S) for both age groups. Treatment response was defined as ≥30% reduction from baseline in total ADHD symptom score. In adolescents (mean age, 13.4 years), atomoxetine improved ADHD significantly compared with placebo (ADHDRS total score change, −12.9 vs −7.5; P < 0.001). In young adults (mean age, 24.7 years), atomoxetine improved ADHD significantly (CAARS total score change, −13.6 vs −7.7; P < 0.001; CGI-ADHD-S change, −1.1 vs −0.6; P < 0.001). No significant treatment-by-age subgroup interaction was observed. Tolerability was similar for both age subgroups, except for treatment-emergent nausea, which occurred significantly more frequently with atomoxetine than with placebo in young adults (13.7% vs 4.8%, respectively; P = 0.024); in adolescents no statistically significant differences were observed in frequency of nausea between atomoxetine and placebo treatment (4.5% vs 10.2%, respectively; P = 0.108). Results from this post hoc, pooled analysis suggest that acute treatment with atomoxetine was efficacious in both adolescent and young adult patients with ADHD. The safety profile findings from this study were consistent with the previously reported atomoxetine safety and tolerability profiles, suggesting that it may be continued during the transition from adolescence to young adulthood.